Complex Systems Fractionality, Time-delay and Synchronization - Luo, Albert C. J.; Sun, Jian-Qiao.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
"Complex Systems: Fractionality, Time-delay and Synchronization" covers the most recent developments and advances in the theory and application of complex systems in these areas. Each chapter was written by scientists highly active in the field of complex systems. The book discusses a new treatise on fractional dynamics and control, as well as the new methods for differential delay systems and control. Lastly, a theoretical framework for the complexity and synchronization of complex system is presented. The book is intended for researchers in the field of nonlinear dynamics in mathematics, physics and engineering. It can also serve as a reference book for graduate students in physics, applied mathematics and engineering. Dr. Albert C.J. Luo is a Professor at Southern Illinois University Edwardsville, USA. Dr. Jian-Qiao Sun is a Professor at the University of California, Merced, USA.
New Treatise in Fractional Dynamics -- Realization of Fractional-Order Controllers: Analysis, Synthesis and Application to The Velocity Control of A Servo-System -- Differential-Delay Equations -- Analysis and Control of Deterministic and Stochastic Dynamical Systems with Time-Delay -- Synchronization of Dynamical Systems in The Sense of Metric Functionals of Specific Constraints.
Keywords: Physics; Systems theory; Vibration; Physics; Nonlinear Dynamics; Systems Theory, Control; Vibration, Dynamical Systems, Control; Systems Theory, Control